Online centralised tourism package system / Ho Ai Ling - Ho , Ai Ling (2006)
The Online Centralised Tourism Package System is developed for the convenience of travel agencies and travelers.Online Centralised Tourism Package System is developed to fulfill the needs of the travel agency as travelers. It aims to centralize tourism packages offered by the local travel agencies, to allow potential tourist to compare the offers and be a smart consumer. It creates a win-win situation, where it gives it gives an opportunity to travel agencies to increase their sales. This proposed system facilitate the online tourism package booking, help to promote Malaysia's tourism industry as well as help the travelers choose appropriate tourism package based on the location, budget, date range desired as well as the activities that they prefer. It is believed that this web based system will gradually become an essential to every travel agency in the future, and help the growth of Business-to-Business and Business to Consumer e-commerce in Malaysia.